Is Export a Probe for Domestic Production? - Saltarelli, Francesco; Cimini, Valeria; Tacchella, Andrea; Zaccaria, Andrea; Cristelli, Matthieu (Frontiers in Physics, 2020)
Recent works leverage export data to assess country production structure and ultimately country relative competitiveness. These works mostly rely only on the exported part of the total country output for reasons of data availability, homogeneity, and quality. Here we use the World Input-Output Database (WIOD), which offers cross-country harmonized data that accounts both for domestic production and export, to investigate to what extent export is a proxy for domestic production. We find that export mirrors remarkably well domestic production for manufacturing sectors or sectors related to physical goods. Conversely, this relation fades away for service related sectors. We found those relations consistently across most of the 40 countries for which data are available.